Investment in the ‘Blue Economy’ of Balochistan: Potential, Prospects, and Policy Options for Improvement in the Light of Global Best Practices - Jamali, Hafeez Ahmed (Journal of Pakistan Administration, 2022)
Pakistan is endowed with a large maritime economic zone whose development can be leveraged to supplement its traditional land-based economy for economic growth and employment generation. Based on international laws and maritime conventions, Pakistan’s Exclusive Economic Zone (EEZ), a part of the sea where Pakistan has exclusive rights over mineral and other economic resources, extends 200 nautical miles from its coastline and comprises an area of 240,000 square kilometers.2 In 2015, the United Nations Commission on the Limits of Continental Shelf (UNCLCS) awarded an additional 150 nautical miles of continental shelf to Pakistan, thereby increasing the size of Pakistan’s EEZ to 290,000 KM.3 This makes Pakistan’s coastal waters and EEZ a virtual fourth largest province/region in terms of area. Based on its marine geology, this maritime region is divided into the Offshore Indus Basin and the Offshore Makran Basin.
Keywords: Blue Economy; Investment; Policy Options; maritime conventions